The effect of prediagnostic aspirin use on the prognosis of stage III colorectal cancer - Kim, Bun (Int J Clin Exp Med, 2015)
Background: Many studies have suggested that the regular use of non-steroidal anti-inflammatory drugs (NSAIDs), including aspirin, has a protective effect and survival benefit on colorectal cancer (CRC). However, recent data suggest that CRCs have different responses to NSAIDs depending on the timing of NSAID initiation, duration of NSAID use, and molecular characteristics of the tumor. The aim of this study was to evaluate the effect of long-term prediagnostic aspirin use on the prognosis of stage III CRC. Methods: From 2007 to 2009, patients who were diagnosed with stage III CRC were recruited, and their medical records were retrospectively analyzed. Patients were divided into prediagnostic aspirin users (who used aspirin for more than three months continuously before CRC diagnosis) and non-users (who did not use of aspirin and NSAIDs). The two groups were compared in terms of recurrence, cancer-specific mortality, disease-free survival (DFS), and cancer-specific survival. In an experimental study, three CRC cell lines (Caco2, SW480, and DLD-1) were pretreated with aspirin (1 mM) for four days or 28 days to make aspirin-resistant cells, treated with 5-fluorouracil (5-FU; 2 µM), and apoptosis was measured with flow cytometry using Annexin-V and propidium iodide double staining. Results: Compared with the aspirin non-users (N=565), the prediagnostic aspirin users (N=121) were not different in terms of baseline characteristics including tumor characteristics, except for comorbidities and diabetes medication and statin use, which were higher in the prediagnostic aspirin users. Recurrence and cancer-specific mortality in stage III CRC were significantly higher in prediagnostic aspirin users than non-users (46.7% vs. 32.3%, P=0.003 and 32.2% vs. 19.8%, P=0.003, respectively). Survival analysis using Cox proportional hazards modeling demonstrated that DFS was significantly worse in prediagnostic aspirin users than non-users (HR, 1.525 (1.018-2.286); P=0.041). In cell line experiments, long-term aspirin pretreatment induced an increase in 5-FU-induced apoptosis in SW480 cells compared with control treatment without aspirin pretreatment. However, Caco2 cells showed a significant decrease of apoptosis in the same experiments and no change in DLD1 cells. Conclusion: Prediagnostic long-term aspirin use in stage III CRC could be a negative prognostic factor depending on the characteristics of the CRC.